DAMPAK PROTOKOL PERSYARATAN HIGENITAS, KARANTINA DAN PEMERIKSAAN INDONESIA-TIONGKOK TERHADAP EKSPOR SARANG BURUNG WALET INDONESIA TAHUN 2018-2020 - Ravi Oktiari; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The purpose of this research is to explain the effect of Indonesia-Tiongkok hygiene, quarantine and inspection requirements protocol on Indonesian swallow nest export commodities. The protocol of requirements to give effect to Indonesian swiftlet nests has hampered the optimization of the export of swallow's nest commodities to Tiongkok. The method used in this research is qualitative. The perspective used by the researcher is the liberalism with the level of analysis of the nation-state. The theory in this research uses the theory of trade barriers. Technique collecting data is taken sourced from books, journals, newspapers, internet and other sources related to the effect of Indonesia-Tiongkok hygiene, quarantine and inspection requirements protocol on the exports of Indonesian swallow nests. The results shows that the effect of hygiene, quarantine and inspection requirements protocol resulted in the export of Indonesian swallow's nests experiencing barriers to optimizing exports, products sanitation, company certification, products quarantine and Tiongkok import quotas. The requirements that have been set must be met by exporters in order to enter the Tiongkok market, exporters who do not meet the requirements for swallow nest commodities will be carried out by Tiongkok. The government's role is expected to help make it easier for exporters of swallow's nests so that they can increase exports of swallow's nests to Tiongkok. Keywords: Export, bird’s Nest, Policy, Trade Barriers